PENGARUH KUALITAS PELAYANAN, TARIF DAN KETEPATAN WAKTU TERHADAP KEPUASAN PELANGGAN (Studi Pada Penumpang Kereta Api Tawang Alun Jurusan Malang-Banyuwangi Di Stasiun Kota Malang) - Niken Oktaviasari; N. Rachma (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT               This study aims to analyze and describe the effect of simultaneous and partial between service quality, tariffs, and timeliness of users of railroad transportation service satisfaction of Tawang alun train customers to Malang-Banyuwangi. The population is the user of the Tawang Alun train majoring in Malang-Banyuwangi at Malang City Station.               The sample of this study was 50 users of the Tawang Alun train service in Malang-Banyuwangi Station in Malang City Station, with the sampling technique using questionnaires and the analysis used in this study was quantitative analysis, with explanatory research.               The results of this study indicate that the variables of service quality, tariff and timeliness are positive and significant to customer satisfaction. Adjusted R square of 0.882 indicates that 88.2% of variance or customer satisfaction is explained by independent variables in the regression equation. While the other 11.8% are explained by other variables not examined in this study.Keywords: Service Quality, Tariff, Timeliness, Customer Satisfaction.